Semianalytical modeling of concrete beams rehabilitated with externally prestressed composites - Mukherjee, Abhijit; Bagadi, S.; Rai, G. (American Society of Civil Engineers, 2009)
This study attempts to develop a semianalytical model for the mechanical behavior of reinforced concrete (RC) beams rehabilitated with externally prestressed carbon fiber-reinforced polymers (CFRP) laminates. The main significance of this study is the model of the process of degradation of RC beams until failure and its recovery through externally prestressed CFRP. Experiments have been carried out to observe the load-deflection behavior of fresh RC beams until the load resistance of the beam is exhausted. The beams have been rehabilitated with external CFRP laminates with varying levels of prestress. The rehabilitated beams have been reloaded until failure. The load-deflection behavior of the fresh and rehabilitated beams has been compared. A model for the load-deflection behavior of the fresh and rehabilitated beam has been proposed. The main import of the model is that it incorporates the effect of confinement of concrete. The model shows very good agreement with the experimental results.